A Novel Case of Marfan Syndrome in an Infant With Hypoplastic Left Heart Syndrome. Issue 5 (September 2019) - Karunanandaa, Aravinth; Plant, Kari Crawford; Herlong, James René; Monteleone, Berrin; Kirshbom, Paul M.; Schwartz, Matthew C.
This report describes a case of hypoplastic left heart syndrome (HLHS) and Marfan syndrome presenting in conjunction, and highlights how a connective tissue disorder may alter medical and surgical management of newborns with HLHS.